The potential use of ebselen in treatment-resistant depression - Ramli, FF; Cowen, PJ; Godlewska, BR (MDPI, 2022)
Ebselen is an organoselenium compound developed as an antioxidant and subsequently shown to be a glutathione peroxidase (GPx) mimetic. Ebselen shows some efficacy in post-stroke neuroprotection and is currently in trial for the treatment and prevention of hearing loss, Meniere’s Disease and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In vitro screening studies show that ebselen is also an effective inhibitor of the enzyme inositol monophosphatase (IMPase), which is a key target of the mood-stabilising drug lithium. Further, in animal experimental studies, ebselen produces effects on the serotonin system very similar to those of lithium and also decreases behavioural impulsivity. The antidepressant effects of lithium in treatment-resistant depression (TRD) have been attributed to its ability to facilitate presynaptic serotonin activity; this suggests that ebselen might also have a therapeutic role in this condition. Human studies utilising magnetic resonance spectroscopy support the notion that ebselen, at therapeutic doses, inhibits IMPase in the human brain. Moreover, neuropsychological studies support an antidepressant profile for ebselen based on positive effects on emotional processing and reward seeking. Ebselen also lowers a human laboratory measure of impulsivity, a property that has been associated with lithium’s anti-suicidal effects in patients with mood disorders. Current clinical studies are directed towards assessment of the neuropsychological effects of ebselen in TRD patients. It will also be important to ascertain whether ebselen is able to lower impulsivity and suicidal behaviour in clinical populations. The objective of this review is to summarise the developmental history, pre-clinical and clinical psychopharmacological properties of ebselen in psychiatric disorders and its potential application as a treatment for TRD.